68.2k views
1 vote
Simplify completely 12x3-4x2+8x / -2x

User Rmsys
by
5.1k points

2 Answers

2 votes

Answer:

-6x² + 2x - 4

Explanation:


(12x^3 - 4x^2 + 8x)/(-2x)

Step 1:

First, group the integers together and divide those:


(12)/(-2) = -6


(-4)/(-2) = 2 (since 4 is also a negative number, you will turn the (-) sign into a (+) sign given the rule that two negatives = a positive.)


(8)/(-2) = -4

Step 2:

Next, group the variables and divide those (when in division, you will subtract the exponents instead of dividing):


(x^3)/(x) = x²


(x^2)/(x) = x (when there is only a variable and no exponent, you can assume 1 as it's exponent.)


(x)/(x) =
x^0 = 0

Step 3:

Combine the integers and variables in the order given and you will get:

-6x² + 2x - 4

User PillarOfLight
by
5.6k points
7 votes

(12x^3-4x^2+8x)/(-2x)=(12x^3)/(-2x)+(-4x^2)/(-2x)+(8x)/(-2x)\\\\=-6x^2+2x-4
User Aditya Mathur
by
5.6k points